Documenting the Purchase of Fuels and Lubricants by the Enterprise (Economics and region, 2021)
The order of documentation of operations on receipt of fuels and lubricants to the enterprise as a result of their acquisition through stationary points on production sites and through third-party gas stations with various forms of calculations is defined. It is found that companies receive fuel and lubricants on the basis of agreements concluded with gas stations, which indicate the brand, type of fuel, its price, the moment of transfer of ownership, method of receipt, place of receipt of fuel. It is established that the implementation and reflection in the accounting of the purchase of fuels and lubricants is influenced by the method of refueling – through gas stations or stationary points at the production sites of the enterprise. Documenting the refueling of motor vehicles through stationary points at the production sites of the enterprise is similar to the registration of the movement of inventories. Documenting the refueling of motor vehicles through gas stations depends on the type of payment (cash or non-cash) and their form (information, coupons, fuel cards). It is reported when purchasing fuel and lubricants by cashless payment without the use of coupons for the release of fuel at the gas station. The peculiarity of the release of fuel on coupons is the restriction of their validity for a certain period. It is established that the modern means of payment for purchased fuel are liter and cash fuel cards, as well as bank payment cards. The authors developed document flow schemes for operations on the receipt of fuel and lubricants when refueling vehicles through stationary points at the production sites of the enterprise and through third-party gas stations in the case of information, coupons, fuel cash and liter cards can be used to improve the accounting of fuel and lubricants at the enterprise.
Keywords: fuels and lubricants; coupons; information; fuel cards; liter cards; documenting of accounting